On the Neotropical spider genus Otoniela Brescovit, 1997 (Araneae: Anyphaenidae, Anyphaeninae), with the description of six new species - Oliveira, Luiz Fernando M.; Alvarenga, José Geraldo G. De; Brescovit, Antonio D. (Zootaxa, 2023)
The genus Otoniela Brescovit, 1997 includes two species, the type species Otoniela adisi Brescovit, 1997, distributed in Peru and Brazil and O. quadrivittata (Simon, 1897), recorded in Venezuela and Argentina. Analyzing 127 individuals permited to expand the records of Otoniela adisi and to describe six additional species: O. lupercioi sp. nov. (♂♀), from Brazil, Argentina and Paraguay; O. chica sp. nov. (♂♀), O. duovizinhense sp. nov. (♂♀), and O. tigre sp. nov. (♂♀), from Brazil and Argentina; and O. aparecida n. sp (♀) and O. negrinho sp. nov. (♂♀), known only from Brazil. As a result, a new emended diagnosis of the genus is presented. Additionally, complementary morphological data of Otoniela adisi are documented.